2007
DOI: 10.1007/s10762-007-9296-7
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-wave Receiver Optics for Korean VLBI Network

Abstract: Over the past several years the millimeter wave VLBI (Very Long Baseline Interferometry) observations have been intensively performed. However phase fluctuation due to troposphere is one of the key issue in terms of degradation of sensitivity and limits imaging capability in millimeter wave VLBI observations. We describe the details of designed receiver optics for the Korean VLBI Network to calibrate tropospheric phase fluctuation for the millimeter wave VLBI observation. These optics guide beams from one posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 5 publications
0
47
0
1
Order By: Relevance
“…The antennas are equipped with the quasi-optic system that allows simultaneous observations at 22, 43, 86, and 129 GHz. This system is described in detail in Han et al (2008).…”
Section: Introduction the Korean Vlbi Network (Kvn) Is The First Dedimentioning
confidence: 99%
“…The antennas are equipped with the quasi-optic system that allows simultaneous observations at 22, 43, 86, and 129 GHz. This system is described in detail in Han et al (2008).…”
Section: Introduction the Korean Vlbi Network (Kvn) Is The First Dedimentioning
confidence: 99%
“…Jung et al (2011) demonstrated the excellence of multi-frequency phase referencing on atmospheric phase compensation in mm-VLBI. Based on this advantage, the KVN (Kim et al 2004;Lee et al 2014) as the first dedicated mm-VLBI array, addresses one of the fundamental limitations of the field, the atmospheric stability, by introducing the simultaneous multi-frequency receiver system (Han et al 2008). The KVN currently consists of three antennas spread across South Korea, located in Seoul and Ulsan in the main land, and in Jeju island.…”
Section: Figurementioning
confidence: 99%
“…The so-called East Asian VLBI Network (EAVN) is expected to be comparable to VLBA or EVN in spatial resolution, sensitivity, and imaging capability (e.g., Yi & Jung 2008). In addition, KVN will be operated in four (22/43/86/129 GHz) different frequency bands simultaneously using multi-frequency band receiver systems (Han et al 2008). Simultaneous multi-frequency observations will make it possible to use the 22 GHz data for performing phase calibrations of higher-frequency data (Jung et al 2011).…”
Section: Korean Vlbi Network (Kvn)mentioning
confidence: 99%